Application Of Computer Technologies In Innovative Educational Activity Of A Teacher - Poniedielnyk, Larysa; Kind-Voitiuk, Nataliia; Shulha, Svitlana; Nesterenko, Nataliia; Chaika, Svitlana; Pakhnenko, Irina (My University, 2022)
The article provides a brief analysis of modern innovations educational technologies in the professional activity of a teacher (distance learning, blended learning, intelligence maps, cloud technologies) and covered at the theoretical level. The article deals with the theoretical and methodological foundations of innovative approaches in the modern education system. The issues of pedagogical support in the modern educational process, new approaches to the problem of the quality of education and assessment of knowledge, problems of management and educational management. Special attention is paid to the study of practical technologies of professional teacher training and activities and innovative areas of professional training specialty students.
Keywords: higher education; competencies; education system; information competence; computer technology